RELATIONSHIP BETWEEN DEMOCRATIC AND INSTRUCTIONAL LEADERSHIP STYLES WITH TEACHERS JOB SATISFACTION IN SELECTED PUBLIC SECONDARY SCHOOLS IN KAGADI DISTRICT. A CROSS-SECTIONAL STUDY. - Ssemata, Swaibu; Sendagi, Muhammad (Student's Journal of Health Research Africa, 2024)
Background: The historical perspective of head teacher's leadership style and teacher job satisfaction in selected public secondary schools can be traced back to the early development of formal education systems. The study aims to assess the relationship between democratic and instructional leadership styles with teachers' job satisfaction. Methodology: A descriptive, correlational, and cross-sectional survey design was undertaken with a mixed approach with both quantitative and qualitative data in 8 secondary schools within Kagadi district. The target population comprised 146 participants which included 08 head teachers and 138 secondary school teachers. Means and standard deviations were also used to analyze data collected on the dependent variable and the dependent variable using the Likert 5-point scale of the responses. Results: The majority of the respondents were male 76%while females were 24%. respondents with 11 and above years of experience constituted the largest group at 39%, followed by those with 6-10 years of experience at 34%, and finally, respondents with 0-5 years of experience at 27%. There was a weak positive correlation between democratic leadership style and teacher job satisfaction (Pearson correlation = 0.311, p = 0.053). Although the correlation is not statistically significant at conventional levels (p < 0.05), there is still a trend indicating a positive relationship. There was a strong positive correlation between instructional leadership style and teacher job satisfaction (Pearson correlation = 0.671, p = 0.021). Conclusion: The strong positive correlation between instructional leadership style and teacher job satisfaction compared to Democratic leadership indicates that instructional leadership practices play a crucial role in shaping teachers' satisfaction levels. Recommendations: Management should promote a culture of transparency, fairness, and accountability in leadership practices, creating a supportive and inclusive environment for all staff members.